Popular Sovereignty in the Framework of Constitutional Philosophy - Yunus, Nur Rohim (ADALAH, 2023)
This essay discusses the concept of popular sovereignty as a primary principle in a democratic system and how it is applied in constitutional philosophy. Popular sovereignty asserts that the highest power lies in the hands of the people and is realised through constitutional mechanisms. However, there are often clashes between the people's will and state policies, especially in law enforcement. Therefore, a strong philosophical, sociological, and legal foundation is needed so that the constitution truly becomes an instrument for protecting people's rights. This essay also proposes several recommendations, such as strengthening public participation, ensuring government transparency, and guaranteeing judicial independence. In addition, political education and constitutional awareness of the community are key to maintaining a healthy democracy. By implementing these steps, popular sovereignty can be realised in a real way in a democratic and just government system.